Use of {99m}Tc-HMPAO Brain SPECT in Patients with Arterial Hypertension: Correlation with Cognitive Function; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Efimova I. Y.; Efimova N. Yu. Nataliya Yurievna; Triss S. V.; Lishmanov Yu. B. Yury Borisovich (Radiation Technologies in Medicine, 2015)
Title screen